Workplace building design and office‐based workers' activity: a study of a natural experiment. (11th October 2015) - Jancey, Jonine M.; McGann, Sarah; Creagh, Robyn; Blackford, Krysten D.; Howat, Peter; Tye, Marian
Abstract: Objective : This opportunistic natural study investigated the effects of relocation of office workers from a 30‐year‐old building to a new purpose‐built building. The new building included an attractive central staircase that was easily accessed and negotiated, as well as breakout spaces and a centralised facilities area. The researchers aimed to determine the impact of the purpose‐built office building on the office workers' sedentariness and level of physical activity. Method : In 2013, a natural pre‐post study was undertaken with office‐based workers in their old conventional 1970s building and on relocating to a new purpose‐built 'activity permissive' building. Objective movement data was measured using accelerometers. Anthropometric and demographic data was also collected. Results : Forty‐two office‐based workers significantly decreased their percentage of daily sitting time (T1 = 84.9% to T2=79.7%; p <0.001) and increased their percentage of daily standing time (T1=11.2% to T2 17.0%; p <0.001) in the new building. Moderate activity significantly declined (T1=3.9% to 3.2%=T2; p =0.038). There was a significant decrease in mean minutes of sitting time (19.62 minutes; p <0.001) and increase in standing time (22.03 minutes; p <0.001). Conclusions : The design of a building can influence activity. This opportunistic study on the impact of workplace relocation on office‐based workers' activity showed modest positive outcomes in sitting and standing. Evidence is required to inform building design policy and practice that supports physical activity and reduces levels of sedentariness in the workplace.